Mining and Selling Radium and Uranium - Robison, Roger F. (Springer International Publishing : Imprint: Springer, 2015)
Presented here is the story of the mining and sale of uranium and radium ore through biographical vignettes, chemistry, physics, geology, geography, occupational health, medical utilization, environmental safety and industrial history. Included are the people and places involved over the course of over 90 years of interconnected mining and sale of radium and uranium, finally ending in 1991 with the abandonment of radium paint and medical devices, Soviet nuclear parity, and the Radiation Exposure Compensation Act.